Local Strongman and Political Dynasty: Political Economic Analysis of Aang Hamid Suganda in Kuningan Regency, 2003-2018 - Kristono, Riyana (JUSS (Jurnal Sosial Soedirman), 2024)
Political dynasty is the inheritance of political power among members of a family over several generations. This study analyzes how political dynasties were built by local strongmen in Kuningan Regency. Kuningan was chosen as the locus of this study on the grounds that in that region a political dynasty was built without experiencing 'resistance' from the residents, and it still continues today. This study uses a qualitative method with a case study approach and is complemented by the use of Joel S. Migdal's theory about local strongman and local bossism from John T. Sidel. The findings were that Aang Hamid Suganda (AHAS) was a local strongman from among successful entrepreneurs and a cadre of PDIP, the political party that won the election in Kuningan. Support for AHAS soared PDIP's rating in Kuningan, symbiotically with his success as Regent for two consecutive terms. The AHAS political dynasty shows that the successful inheritance of power within a family can be done through the effectiveness of political strategy, the significance of regional development, and the strong social influence created.